2015
DOI: 10.1002/bbb.1578
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal liquefaction of bagasse using ethanol and black liquor as solvents

Abstract: The objective of this study was to examine the hydrothermal liquefaction of sugarcane bagasse using ethanol and black liquor (BL) in a pilot scale. Combinations of co-solvents (ethanol/ water, ethanol/BL) were studied at various concentrations and reaction conditions. The maximum oil yield of 61% was achieved with a reaction temperature of 300 °C for 30 min and using pure BL as a solvent, while the highest higher heating value (HHV) was obtained from a 50:50 ethanol-BL mixture. The oils contained alcohols, est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…Use of such catalysts in some studies has led to substantial increases in biocrude yields and increased biocrude quality. 20,28 Organic solvents used in HTL generally involve the use of alcohols (generally ethanol), either alone or in aqueous mixtures, 13,16,21,25,32 although other solvents such at heptane and toluene have also been used when in situ fractionation of the biocrude was desired. 26 Using organic solvents, either in neat form or as cosolvents, has been shown to significantly increase biocrude yields.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of such catalysts in some studies has led to substantial increases in biocrude yields and increased biocrude quality. 20,28 Organic solvents used in HTL generally involve the use of alcohols (generally ethanol), either alone or in aqueous mixtures, 13,16,21,25,32 although other solvents such at heptane and toluene have also been used when in situ fractionation of the biocrude was desired. 26 Using organic solvents, either in neat form or as cosolvents, has been shown to significantly increase biocrude yields.…”
Section: Resultsmentioning
confidence: 99%
“…26 Using organic solvents, either in neat form or as cosolvents, has been shown to significantly increase biocrude yields. 13,21,25 However, one study reported that lower biocrude quality accompanied the higher yields. 21 When an alcohol is used as the sole solvent, it has the advantage that HTL can be performed under supercritical conditions at much lower temperatures and pressures compared to using water as a solvent.…”
Section: Resultsmentioning
confidence: 99%
“…Correlations state that heating value is directly proportional with the elemental composition, with carbon and hydrogen increasing heating value and oxygen and nitrogen having a negative effect [54]. However, it is the experience of the authors that traditional correlations do not closely match experimental data for HTL bio-crudes [39,40] and so existing correlations should be modified. While HHV quantity is not regulated, it is prudent to produce biofuels with heating values similar to conventional fuels to ensure minimal modifications to engines, particularly in injection technology.…”
Section: Heating Valuementioning
confidence: 99%
“…HTL operates at higher pressures than other thermochemical techniques with 200-300 bar not uncommon. The key advantage of HTL over pyrolysis is that the feedstock can be processed without any pre-drying [70][71][72] but yields of liquid fuel are also quite high. However, the fuel properties of the bio-oil resulting from HTL are poor for transportation vehicles compared to that of diesel.…”
Section: Hydrothermal Liquefactionmentioning
confidence: 99%